Psychophysiological effects of oxytocin on parent–child interactions: A literature review on oxytocin and parent–child interactions. Issue 10 (11th July 2017) - Szymanska, Monika; Schneider, Marie; Chateau‐Smith, Carmela; Nezelof, Sylvie; Vulliez‐Coady, Lauriane
Abstract : Oxytocin (OT), often called the 'hormone of love' or 'hormone of attachment, ' plays a fundamental role in the establishment and quality of parent–infant bonding. However, emerging evidence indicates that OT can also produce antisocial behavior. To clarify these effects, we review studies examining the role of endogenous and exogenous OT on several determinants of attachment: parental sensitivity, and bonding or synchrony in parent–child dyads. Contextual and individual factors moderating the effect of intranasal OT and its peripheral levels are also reviewed. Finally, potential therapeutic applications for OT and current limitations in human OT research are examined. This systematic literature review was based on the Preferred Reporting Items for Systematic reviews and Meta‐Analyses (PRISMA) guidelines, with two electronic databases and other bibliographic sources. We identified a total of 47 relevant studies for inclusion in our review. Most of the findings are in accordance with recent ideas that OT administration may increase parent–child prosocial interaction, showing that OT exerts beneficial effects on processes thought to promote bonding, sensitivity, and synchrony. However, we found that OT can induce antisocial behavior (e.g., anxiety) or adverse effects (modulation of maternal care recollections) that are moderated by different contextual (e.g., maltreatment level, presence of unfamiliar people) and individual (attachment style) factors. This review reinforces the importance of context‐ and individual‐dependent factors, which must be taken into account when analyzing the psychophysiological effects of OT.